2011
DOI: 10.4103/1477-3163.78279
|View full text |Cite
|
Sign up to set email alerts
|

The AOM/DSS murine model for the study of colon carcinogenesis: From pathways to diagnosis and therapy studies

Abstract: Colorectal cancer (CRC) is a major health problem in industrialized countries. Although inflammation-linked carcinogenesis is a well accepted concept and is often observed within the gastrointestinal tract, the underlying mechanisms remain to be elucidated. Inflammation can indeed provide initiating and promoting stimuli and mediators, generating a tumour-prone microenvironment. Many murine models of sporadic and inflammation-related colon carcinogenesis have been developed in the last decade, including chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
213
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 455 publications
(226 citation statements)
references
References 129 publications
(173 reference statements)
12
213
1
Order By: Relevance
“…Among the chemically induced colitis-associated cancer (CAC) mouse models, a single injection with azoxymethane (AOM) is followed by cyclic treatment with DSS [65,66]. In this model, besides the genetic background of the mice, a number of other factors contribute to the development and progression of the disease.…”
Section: Multiple Factors Affect Colitis-associated Cancer Developmenmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the chemically induced colitis-associated cancer (CAC) mouse models, a single injection with azoxymethane (AOM) is followed by cyclic treatment with DSS [65,66]. In this model, besides the genetic background of the mice, a number of other factors contribute to the development and progression of the disease.…”
Section: Multiple Factors Affect Colitis-associated Cancer Developmenmentioning
confidence: 99%
“…Furthermore, both male and female mice develop DSS-induced colitis robustly; however, the males rapidly develop more significant and aggressive disease than the age-matched females. Thus, the development of DSS-induced colitis in mouse models and its severity may depend on the genetic background of mice, their gut microbiome composition, sex, and sex hormone levels [65][66][67].…”
Section: Multiple Factors Affect Colitis-associated Cancer Developmenmentioning
confidence: 99%
See 1 more Smart Citation
“…Azoxymethane (AOM), a metabolite of 1,2-dimethylhydrazine (DMH), is a colon cancer inducing agent, which serves as a tool to evaluate colon tumour in rats and mice (Chan et al 2006). AOM has likewise been utilized as a part of the investigation of the preventive efficacy of numerous natural products on colon cancer (De Robertis et al 2011). It has been reported that the liver and lungs are the most affected organs during colon cancer induction using AOM (Chan et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Adult male BALB/c mice were intraperitoneal injected with Azoxymethane (AOM)10 mg/Kg body weight and a week later, Dextran Sodium Sulphate (DSS) was given in the drinking water for seven days following the procedure reviewed by Rosenberg et al (2009) [12], Tanaka (2009) [13] and De Robertis et al, (2011) [14]. Control animal were injected with saline solution and were not given DSS.…”
Section: Murine Model Of Chemical-induced Colon Cancer (Aom/dss)mentioning
confidence: 99%